Variations in Pesticide Doses under Field Conditions: Pesticide dose variation - Velini, E. D. [UNESP] (2017)
Pesticide doses are most commonly expressed by the volume or weight of the pesticide applied to an area (usually onehectare). However, many plants, insects or microbes can complete their life cycles in environments of only a few cm or mm. Pesticide doses are not uniform in the field and, on such a small scale, some target organisms survive because they do not receive enough pesticide. Highly variable doses within a field can also contribute to the selection of resistant biotypes, and some target organisms receive doses low enough to show hormesis. The information available consistently shows highly variable pesticide deposition or concentrations in individual leaves, plants (crops or weeds) and soil samples. Because of dose variability in the field, higher mean doses are necessary to achieve satisfactory control levels. Weeds compete for spray droplets, and higher weed populations can reduce the individual doses deposited. The presence of heterogeneous amounts of straw on the soil can contribute to increased variation in the doses of pre-emergence herbicides and the possibility of other classes of pesticides being transported to the soil by rain water.